An active HIV reservoir during ART is associated with maintenance of HIV-specific CD8+ T cell magnitude and short-lived differentiation status - Hiroshi Takata; Julie L. Mitchell; Julián Avila Pacheco; Amélie Pagliuzza; Suteeraporn Pinyakorn; Supranee Buranapraditkun; Carlo Sacdalan; Louise Leyre; Sam Nathanson; Juyeon C. Kakazu; Jintana Intasan; Peeriya Prueksakaew; et al. (2023)
Before initiation of antiretroviral therapy (ART), HIV-specific CD8+ T cells are dysfunctional and short lived. To better understand the relationship between the HIV reservoir in CD4+ T cells and the magnitude and differentiation status of HIV-specific CD8+ T cells, we investigated these cells from acute and chronic HIV-infected individuals after 2 years of ART. Although both the HIV reservoir and the CD8+ T cell responses declined significantly after 2 years of ART, sustained HIV-specific CD8+ T cell responses correlated with a greater reduction of integrated HIV provirus. However, the magnitude of CD8+ T cells specific for HIV Gag, Pol, Nef, and Vif proteins positively associated with the active reservoir size during ART, measured as cell-associated RNA. Importantly, high HIV DNA levels strongly associate with maintenance of short-lived HIV-specific CD8+ T cells, regardless of ART initiation time. Our data suggest that the active reservoir maintains HIV-specific CD8+ T cell magnitude but prevents their differentiation into functional cells.